Doživljanje žensk, obolelih za rakom dojke, in načini pomoči medicinskih sester - Šmit, Majda (Obzornik zdravstvene nege, 2004)
In the article psychosocial impact of breast cancer on patients are presented.Theoretical part presents the crisis situation occurring when the disease is diagnosed. It can occur at the very suspicion that the disease might be malignant, and can proceed through periods of diagnostic process, treatment, rehabilitation, prolonged survival and relapse. The impact of the disease on self-image and self-respect is also presented. The article also describes experience of the author herself at her home following discharge andpresents confrontation of patients with their own morbidity and mortality. The role of the nurse in psychological support is stressed. In the conclusion the author presents the needs and importance of further postgraduate forms of training for nursing care of patients with breast cancer (breast cancer nurse)in the frames of oncological nursing care in Slovenia.
Keywords: Body Image; bolniki; breast; Breast Neoplasms; čustva; Dojka, novotvorbe; dojke; doživljanje bolezni; kirurško zdravljenje; medicinske sestre; Nursing; psihologija; Psychology; rak (medicina); Samokoncept; samopodoba; Self Concept; Telesna podoba